Sulfotransferase and Heparanase: Remodeling Engines in Promoting Virus Infection and Disease Development - Kaltenbach, Dominik D.; Jaishankar, Dinesh; Hao, Meng; Beer, Jacob C.; Volin, Michael V.; Desai, Umesh R.; Tiwari, Vaibhav (Frontiers in Pharmacology, 2018)
An extraordinary binding site generated in heparan sulfate (HS) structures, during its biosynthesis, provides a unique opportunity to interact with multiple protein ligands including viral proteins, and therefore adds tremendous value to this master molecule. One such example is the sulfation at the C3 position of glucosamine residues in HS chain via 3-O sulfotransferase (3-OST) enzymes, which generates a unique virus-cell fusion receptor during herpes simplex virus (HSV) entry and spread. Emerging evidence now suggests that the unique patterns in HS sulfation assist multiple viruses in invading host cells at various steps of their life cycles. In addition, sulfated-HS structures are known to assist in invading host defense mechanisms and initiating multiple inflammatory processes; a critical event in the disease development. All these processes are detrimental for the host and therefore raise the question of how HS-sulfation is regulated. Epigenetic modulations have been shown to be implicated in these reactions during HSV infection as well as in HS modifying enzyme sulfotransferases, and therefore pose a critical component in answering it. Interestingly, heparanase (HPSE) activity is shown to be upregulated during virus infection and multiple other diseases assisting in virus replication to promote cell and tissue damage. These phenomena suggest that sulfotransferases and HPSE serve as key players in extracellular matrix remodeling and possibly generating unique signatures in a given disease. Therefore, identifying the epigenetic regulation of OST genes, and HPSE resulting in altered yet specific sulfation patterns in HS chain during virus infection, will be a significant a step towards developing potential diagnostic markers and designing novel therapies.